Roughened silver microtubes for reproducible and quantitative SERS using a template-assisted electrosynthesis approach. (September 2020) - Perales-Rondon, Juan V.; Colina, Alvaro; González, María Cristina; Escarpa, Alberto
Highlights: Successful preparation of silver microtubes SERS substrates by template-assisted electrosynthesis approach. Intrinsic roughness that enhance the SERS capability of the as synthesized silver microtube SERS substrates. Remarkable reproducibility of the SERS measurements with promising quantitative applications. Abstract: The synthesis and application of silver microtube substrates for quantification by surface enhanced Raman spectroscopy (SERS) is presented in this work. The roughened silver microtubes were prepared by template assisted electrosynthesis method. Using rhodamine 6G as a Raman probe molecule, the silver microtubes were tested for SERS determination, demonstrating a high performance for quantitative analysis with high precision and low data dispersion (%RSD < 3), which is the limiting step in quantitative SERS. This performance can be explained by obtaining a single silver microtube substrate highly homogeneous in SERS activity in the whole surface and with high reproducibility between different synthesis batches. Graphical abstract: Image, graphical abstract